Modulating biochar compositions to maximize synergy between contaminant binding and transformation: the critical role of carbonates and implications for in situ groundwater remediation - Lin Duan; Zicui Gong; Yang Li; Tianchi Cao; Tong Zhang; Wei Chen (Biochar)
Abstract Dealing with groundwater impacted by persistent, low-concentration chlorinated solvents is a major challenge for site remediation, as technologies designed for fast contaminant removal or destruction often are not cost-effective. For long-term plume management, in situ contaminant sequestration using carbonaceous materials is a more viable strategy. Here, we prove the concept that the effectiveness of this approach can be improved by modulating the compositional and surface properties of carbonaceous materials to maximize the synergy between contaminant binding and abiotic transformation. We found that two pine wood biochars pyrolyzed at 600 and 700 °C exhibit not only faster adsorption kinetics for 1,1,2,2-tetrachloroethane than those prepared at lower temperatures (500 °C and below), but also greater efficacy in enhancing the dehydrochlorination of the contaminant. The higher catalytic efficiency is counterintuitive, as it is commonly accepted that surface carboxyl and phenolic groups are the catalytic sites. With supplementary experiments carried out using modified materials and at varied pH values, we found that the surprisingly higher catalytic activities of these two samples are due to their higher carbonate contents. Interestingly, trichloroethylene, the hydrolysis product, is more adsorptive to the biochars than the parent compound. Thus, by promoting the abiotic transformation, these two biochars enable much more effective plume interception than the less-reactive materials. The findings have important implications for dealing with long-term, persistent groundwater contamination, particularly, the “rebounding” problem often occurring post active site remediation. Graphical Abstract